2015
DOI: 10.1007/s11999-015-4461-0
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening With External Fixation Is Effective in Congenital Femoral Deficiency

Abstract: Background Treatment of congenital femoral deficiency is a complex, multistage protocol and a variety of strategies have been devised to address joint instability, limb length inequality, and deformities. Despite being an important part of the algorithmic approach to the overall treatment of patients with congenital femoral deficiency, a reproducible, safe, and functional treatment for femoral length discrepancy in patients with mild and moderate congenital femoral deficiency has not been reported. Questions/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
(56 reference statements)
1
20
1
5
Order By: Relevance
“…Indeed, Jones et al reported only eight cases of knee subluxation in a total of 329 related studies. 12 However, depending on the limb elongation technique this rate may increase, as observed after the monolateral external fixator technique (13%), 15 the transarticular Ilizarov technique (30%), 16 and the Wagner technique (33.0–43.5%). 12 , 13 Indeed, this current review showed a similar distribution of knee subluxation according to each referred technique.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Jones et al reported only eight cases of knee subluxation in a total of 329 related studies. 12 However, depending on the limb elongation technique this rate may increase, as observed after the monolateral external fixator technique (13%), 15 the transarticular Ilizarov technique (30%), 16 and the Wagner technique (33.0–43.5%). 12 , 13 Indeed, this current review showed a similar distribution of knee subluxation according to each referred technique.…”
Section: Discussionmentioning
confidence: 99%
“…8 El 2015 Prince publica su serie de 30 pacientes con alargamiento de fémur con técnica LON por fémur corto congénito, con al menos 2 años de seguimiento, mostró buenos resultados en cuanto a función y comodidad, sin embargo, en pacientes con alargamientos mayores a 6 cm o 25% se obtuvieron peores resultados en cuanto al dolor y a la funcionalidad. 9 El alargamiento sobre CIM en tibia ha tenido una amplia difusión. En 1999 Kristiansen publica su experiencia con 9 casos de alargamiento de tibia, sin embargo, con regulares resultados y frecuente refractura.…”
Section: Discussionunclassified
“…Так, при ишемическом по-ражении промежуточной широчайшей мышцы нарушается функция скольжения четырехглавой мышцы; постоянная компрессия суставных хря-щей ведет к нарушению его трофики и развитию хондропатии. В зависимости от величины уд-линения полная функциональная реабилитация наступает обычно через 9-18 месяцев после снятия аппарата [12,13,14].…”
Section: Discussionunclassified